A case of robot‐assisted laparoscopic partial nephrectomy during pregnancy - Kenji Tsutsui; Airi Miki; Teppei Wakita; Yuki Horibe; Masaru Tani; Yoichi Kakuta; Koichi Tsutahara; Tetsuya Takao (IJU Case Reports, 2023)
Introduction Malignancy during pregnancy requires consideration of both the mother and fetus. We report a patient with renal cell carcinoma during pregnancy who was treated with robot‐assisted partial nephrectomy. Case presentation The patient was incidentally found to have a renal mass on abdominal ultrasonography. Definitive diagnosis of cT1aN0M0 RCC was made by enhanced computed tomography. Subsequently, pregnancy was discovered. RAPN was performed without complications. Pathologic examination revealed clear cell RCC. There were no postoperative complications, and the baby was born safely. Conclusion RAPN can be safe and effective even during pregnancy. Every pregnant patient requires individualized treatment involving the timing of surgery, the procedure used, and management based on the condition of the mother and fetus, tumor stage, and the experience of the surgical team.